Making visible the invisible - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Women in developing economies: making visible the invisible edited by Joycelin Massiah 1993 300pp ISBN 0 85496 346 4 (BERG)